Enclosures of Wind: Practice-Led Methods for Visualization of Elemental Media - Abelardo Gil-Fournier; Jussi Parikka (Media + Environment)
This article engages with the aesthetics of air as it becomes spatialized, managed, and rescaled across different material configurations in the context of an art exhibition. The text builds an argument concerning wind, air currents, and cultural techniques of visualization and circulation through a live curatorial and artistic example of Abelardo Gil-Fournier's exhibition *The Raft: Three Acts for an Exposure to the Elements* at the Fundación Cerezales Antonino y Cinia (FCAYC) in León, Spain, in 2023--24. The spatial setting of the exhibition and its relation to the surrounding valley are investigated through imaging, modeling, and acoustic resonance that frame questions of air, atmosphere, and wind through the processual methodology employed. The article thus does not focus on final artworks so much as on the process of constructing an exhibition where issues of curatorial practice, architectural considerations, and practice-led research feature together with an undercurrent of arguments drawing on recent media theory as well as the history of media and science. In focusing on the framing of air and wind, the article asks: How do material limitations and conditions of curatorial practice address multiscalar planetary space? The article is structured around the broader theoretical point that responds to the core questions of this special issue and the three acts that structure the exhibition as an investigation of material methods of movement of bodies and air, spatial enclosures and their outsides.